A dual-function transcription factor, SlJAF13, promotes anthocyanin biosynthesis in tomato. (11th May 2022) - Chen, Yunzhu; Kim, Pyol; Kong, Lingzhe; Wang, Xin; Tan, Wei; Liu, Xin; Chen, Yuansen; Yang, Jianfei; Chen, Bowei; Song, Yuxin; An, Zeyu; Min Phyon, Jong; et al.
Abstract : SlJAF13 promotes anthocyanin synthesis in tomato by activating SlAN1, a gene encoding a member of MBW complex, and by suppressing SlJAZ2, which inhibits the MBW complex. Abstract: Unlike modern tomato ( Solanum lycopersicum ) cultivars, cv. LA1996 harbors the dominant Aft allele, which is associated with anthocyanin synthesis in tomato fruit peel. However, the control of Aft anthocyanin biosynthesis remains unclear. Here, we used ethyl methanesulfonate-induced and CRISPR/Cas9-mediated mutation of LA1996 to show, respectively, that two class IIIf basic helix–loop–helix (bHLH) transcription factors, SlJAF13 and SlAN1, are involved in the control of anthocyanin synthesis. These transcription factors are key components of the MYB–bHLH–WD40 (MBW) complex, which positively regulates anthocyanin synthesis. Molecular and genetic analyses showed that SlJAF13 functions as an upstream activation factor of SlAN1 by binding directly to the G-Box motif of its promoter region. On the other hand, SlJAZ2, a JA signaling repressor, interferes with formation of the MBW complex to suppress anthocyanin synthesis by directly binding these two bHLH components. Unexpectedly, the transcript level of SlJAZ2 was in turn repressed in a SlJAF13-dependent manner. Mechanistically, SlJAF13 interacts with SlMYC2, inhibiting SlMYC2 activation of SlJAZ2 transcription, thus constituting a negative feedback loop governing anthocyanin accumulation. Taken together, our findings support a sophisticated regulatory network, in which SlJAF13 acts as an upstream dual-function regulator that fine tunes anthocyanin biosynthesis in tomato.